2016
DOI: 10.1242/dev.144105
|View full text |Cite
|
Sign up to set email alerts
|

Wt1 directs the lineage specification of sertoli and granulosa cells by repressing Sf1 expression

Abstract: Supporting cells (Sertoli and granulosa) and steroidogenic cells (Leydig and theca-interstitium) are two major somatic cell types in mammalian gonads, but the mechanisms that control their differentiation during gonad development remain elusive. In this study, we found that deletion of Wt1 in the ovary after sex determination caused ectopic development of steroidogenic cells at the embryonic stage. Furthermore, differentiation of both Sertoli and granulosa cells was blocked when Wt1 was deleted before sex dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 43 publications
4
69
0
Order By: Relevance
“…Down-regulation of Dhh transcripts in Wt1 vivo -morpholino treated XY gonadal explants (Fig 6A) is in line with a previous report of reduced Dhh expression in Wt1 -deficient testes of adult mice [39]. Furthermore, our findings corroborate a most recent study illustrating decreased Dhh mRNA levels in Wt1 -deficient testes at E13.5 [61]. By demonstrating that WT1 knockdown also decreased Gli1 , Gli2 , Ptch1 and Smo transcripts in embryonic XY gonads (Fig 6A), our findings suggest that WT1 activates the HH pathway at multiple stages.…”
Section: Discussionsupporting
confidence: 93%
“…Down-regulation of Dhh transcripts in Wt1 vivo -morpholino treated XY gonadal explants (Fig 6A) is in line with a previous report of reduced Dhh expression in Wt1 -deficient testes of adult mice [39]. Furthermore, our findings corroborate a most recent study illustrating decreased Dhh mRNA levels in Wt1 -deficient testes at E13.5 [61]. By demonstrating that WT1 knockdown also decreased Gli1 , Gli2 , Ptch1 and Smo transcripts in embryonic XY gonads (Fig 6A), our findings suggest that WT1 activates the HH pathway at multiple stages.…”
Section: Discussionsupporting
confidence: 93%
“…In WT1‐deficient XY gonads of mice at E13.5, the downregulation of WT1 increased the levels of mRNA for StAR , CYP11A1 , 3β‐HSD , and CYP17A1 (Chen et al, ); however, in ovaries from 3‐week‐old mice, a WT1 mutation had no effect on the levels of mRNA for CYP11A1 and 3β‐HSD in granulosa cells (Gao et al, ). In our study, the downregulation of WT1 increased the level of mRNA for 3β‐HSD but had no effect on the level of mRNA for StAR , CYP11A1 , or CYP17A1 in adult cortical stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The differences may also be explained by the differences in cell types and stages of development. Previous studies have shown that 3β‐HSD‐positive cells are steroidogenic cells, such as theca‐interstitial cells, and that the 3β‐HSD expression level represents the degree of steroidogenic cell differentiation (Chen et al, ; Honda et al, ; Jeays‐Ward et al, ). In our study, the expression of 3β‐HSD in the cortical stroma was significantly lower than that in the theca layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations